2017
DOI: 10.24167/celt.v16i2.487
|View full text |Cite
|
Sign up to set email alerts
|

Figuring the Context of CTL under 2013 Curiculum

Abstract: The 2013 curriculum states that the purpose of teaching English for junior high school is to develop students’ communicative competence. In line with this expectation, several learning characteristics have been defined i.e. learning from model, observing, questioning, gathering information, associating, and communicating. Therefore, the teaching approaches that are used by the teacher in teaching English must suit the criteria to promote students' communicative competence. Contextual Teaching and learning (CTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…This view supported theory by Rokni & Karimi (2013) that using picture in teaching EFL class attracted the students for better learning. Besides, this data also supported Naseer, Fata, Daud, & Isniati, (2016) stating that pictures are attractive for students also using pictures help teacher to overcome the problems of translation.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This view supported theory by Rokni & Karimi (2013) that using picture in teaching EFL class attracted the students for better learning. Besides, this data also supported Naseer, Fata, Daud, & Isniati, (2016) stating that pictures are attractive for students also using pictures help teacher to overcome the problems of translation.…”
Section: Resultssupporting
confidence: 73%
“…This is one of steps of scientific approach in curriculum 2013. Naseer et al (2016) revealed that in scientific approach the first step is observation. In this step the teacher ask students to observe about the lesson that they learn.…”
Section: Resultsmentioning
confidence: 99%
“…Long-life education is a concept where Iindividuals will always learn along with their life since education is life itself (Nasir et al, 2017;Waseso, 2018), known as a long-life education. .In line with education's main purpose, life-long learning is seen as a continuous lifetime experience that leads individuals for self-development and autonomous (Candy, 1991;Holec, 1981;Little, 2007;Littlewood, 2017).…”
mentioning
confidence: 99%
“…In Indonesia, the concept of learner autonomy is reflected in its Foundation of Education, including philosophical, sociological, and ICT (Claramita, 2016;Zainuddin, 2015). Learner autonomy through the implementation of Curriculum 2013 proves that the foundation of education in Indonesia is based on Constructivism as one of the Philosophical Educational Foundation (Nasir et al, 2017;Waseso, 2018). Constructivists view education as the freedom and opportunity of learners to make a choice (Borisov, 2014).…”
mentioning
confidence: 99%
“…Encouraging students to learn English is a challenge for teachers especially for students who do not have special goals and feel no need to learn them [4]. The aim for learning English is to develop students' communicative competence in English both oral and written [5]. Games can also be a medium for distributing education to players [6].…”
Section: Introductionmentioning
confidence: 99%